A sensor classification scheme of robotic manipulators using multidimensional scaling technique - Lima, Miguel F. M. (2019)
This paper analyzes the signals captured during impacts and vibra-tions of a mechanical manipulator. To test the impacts, a flexible beam is clamped to the end-effector of a manipulator that is programmed in a way such that the rod moves against a rigid surface. Eighteen signals are captured and theirs correlation are calculated. A sensor classification scheme based on the multidimensional scal-ing technique is presented.